UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) SISWA KELAS V MATERI LUAS BANGUN DATAR DENGAN MEDIA KONGKRIT SDN MI ISLAMIYAH 01 KOTA MADIUN - Anang Adiwijaya; Indra Cahaya; Agsa Nalendra Raditya Wardhana; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the cognitive learning outcomes of fifth-grade students of MI Islamiyah 01 Madiun City on the topic of area of ​​flat shapes through the application of the Realistic Mathematics Approach (RMAT) assisted by concrete media. The method used is the Kurt Lewin Classroom Action Research (CAR) model which includes the stages of planning, action, observation, and reflection. The research subjects consisted of 12 students. Data were collected through observation, tests, documentation, and interviews. The results in the pre-cycle stage showed that most students had not reached the Minimum Completion Criteria (KKM), with a percentage of completion of only 8.33%. After the actions were carried out in the first cycle, the completion rate increased to 50%, although it did not meet the target. Through learning improvements in the second cycle, all students successfully achieved the KKM (100%) with an average score of 89.17. The application of RMAT and concrete media has been proven to improve students' understanding of the concept of area of ​​flat shapes, making learning more contextual and enjoyable. Thus, this approach is effective in improving students' mathematics learning outcomes and is recommended for use in learning concrete materials.